A tribute to resistance: Eugenia quilombola (Myrtaceae), a new species with multilocular anthers from the Atlantic Forest of northeastern Brazil - Amorim, Bruno S.; de Souza, Maria Anália Duarte; Albuquerque, Patrícia Melchionna; Negrão, Raquel; Giaretta, Augusto (Phytotaxa, 2022)
Eugenia quilombola, a new species restricted to the northern portion of the Atlantic Forest is here described. Its sheets were previously misidentified as Eugenia umbrosa and this misquoting name have been used in scientific collections and publications until now. After 10 years of studies and discussions about its identity, Eugenia quilombola was recognized as a new taxon based on its diagnostic features of multilocular anthers and verrucose fruits (vs. rimose anther and smooth fruit in E. umbrosa). Furthermore, Eugenia quilombola has a narrow distribution in northeastern Brazil while E. umbrosa occurs in the southeastern region and in the state of Bahia.